2021
DOI: 10.1002/app.50596
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyvinylpyrrolidone/graphene oxide/epoxy resin composite coatings and the study on their anticorrosion performance

Abstract: Waterborne epoxy resin (EP) is often used as anticorrosive coating in the industrial field. However, small holes and gaps can be formed during the curing process. The corrosive medium easily penetrates the anticorrosive coating and corrodes the metal matrix. Herein, polyvinylpyrrolidone (PVP) and graphene oxide (GO) were doped into EP to improve the shielding and resistance to corrosive media. The composite coatings were prepared successfully by solution blending method. In the PVP/GO composite materials, orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Many methods have been attempted to protect the metallic surface against corrosion, for example, polymeric coatings [3], inorganic coatings [4], hydrid coatings [5], self-healing smart coatings [6],…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been attempted to protect the metallic surface against corrosion, for example, polymeric coatings [3], inorganic coatings [4], hydrid coatings [5], self-healing smart coatings [6],…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In order to improve the corrosion resistance of epoxy coatings and prolong their service life, common modification methods include chemical modification (such as silicone, 5 acrylic acid 6 ) and filler modification. [7][8][9][10] Corrosion of materials is related to the properties and microstructure of surface coatings. Studies have found that adding nanofillers to organic coatings can effectively enhance their wear resistance, corrosion resistance, and aging resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the corrosion resistance of epoxy coatings and prolong their service life, common modification methods include chemical modification (such as silicone, 5 acrylic acid 6 ) and filler modification 7–10 . Corrosion of materials is related to the properties and microstructure of surface coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been attempted to protect the metallic surface against corrosion, for example, polymeric coatings [3], inorganic coatings [4], hydrid coatings [5], self-healing smart coatings [6], photocathodic protection [7] and so on. Among them, the polymeric coatings are more popularly used for the protection of metallic surface, which can form a protective barrier to inhibit the penetration of corrosive media including H 2 O, O 2 and other ions.…”
Section: Introductionmentioning
confidence: 99%